Activation energy for Cu-Sn intermetallic in CNT-reinforced Sn-1.0Ag-0.5Cu solder. Issue 2 (6th November 2019) - Mayappan, Ramani; Salleh, Amirah; Tokiran, Nurul Atiqah; Awang, N.A.
Abstract : Purpose: The purpose of this study is to investigate the addition of 0.05 Wt.% carbon nanotube (CNT) into the Sn-1.0Ag-0.5Cu (SAC) solder on the intermetallic (IMC) growth. Lead-based solders play an important role in a variety of applications in electronic industries. Due to the toxicity of the lead in the solder, lead-free solders were proposed to replace the lead-based solders. Sn-Ag-Cu solder family is one of the lead-free solders, which are proposed and considered as a potential replacement. Unfortunately, the Sn-Ag-Cu solder faces some reliability problems because of the formation of the thick intermetallic compounds. So the retardation of intermetallic growth is prime important. Design/methodology/approach: The solder joint was aged under liquid state aging with soldering time from 1 to 60 min. Findings: Two types of intermetallics, which are Cu6 Sn5 and Cu3 Sn were observed under a scanning electron microscope. The morphology of Cu6 Sn5 intermetallic transformed from scallop to planar type as the soldering time increases. The addition of carbon nanotube into the SAC solder has retarded the Cu6 Sn5 intermetallic growth rate by increasing its activation energy from 97.86 to 101.45 kJ/mol. Furthermore, the activation energy for the Cu3 Sn growth has increased from 102.10 to 104.23 kJ/mol. Originality/value: The increase in the activation energy indicates that the growth of the intermetallics was slower. This implies that the addition of carbon nanotube increases the reliability of the solder joint and are suitable for microelectronics applications.